Virtual reality improves embodiment and neuropathic pain caused by spinal cord injury. (31st October 2017) - Pozeg, Polona; Palluel, Estelle; Ronchi, Roberta; Solcà, Marco; Al-Khodairy, Abdul-Wahab; Jordan, Xavier; Kassouha, Ammar; Blanke, Olaf
Abstract : Objective: To investigate changes in body ownership and chronic neuropathic pain in patients with spinal cord injury (SCI) using multisensory own body illusions and virtual reality (VR). Methods: Twenty patients with SCI with paraplegia and 20 healthy control participants (HC) participated in 2 factorial, randomized, repeated-measures design studies. In the virtual leg illusion (VLI), we applied asynchronous or synchronous visuotactile stimulation to the participant's back (either immediately above the lesion level or at the shoulder) and to the virtual legs as seen on a VR head-mounted display. We tested the effect of the VLI on the sense of leg ownership (questionnaires) and on perceived neuropathic pain (visual analogue scale pain ratings). We compared illusory leg ownership with illusory global body ownership (induced in the full body illusion [FBI]), by applying asynchronous or synchronous visuotactile stimulation to the participant's back and the back of a virtual body as seen on a head-mounted display. Results: Our data show that patients with SCI are less sensitive to multisensory stimulations inducing illusory leg ownership (as compared to HC) and that leg ownership decreased with time since SCI. In contrast, we found no differences between groups in global body ownership as tested in the FBI. VLI and FBI were both associated with mild analgesia that was only during the VLI specific for synchronous visuotactile stimulation and the lower back position. Conclusions: The present findings show that VR exposure using multisensory stimulation differently affected leg vs body ownership, and is associated with mild analgesia with potential for SCI neurorehabilitation protocols.